Increasing the Amount and Intensity of Stepping Training During Inpatient Stroke Rehabilitation Improves Locomotor and Non-Locomotor Outcomes. (September 2022) - Henderson, Christopher E.; Plawecki, Abbey; Lucas, Emily; Lotter, Jennifer K.; Scofield, Molly; Carbone, Angela; Jang, Jeong H.; Hornby, T. George
Background: The efficacy of traditional rehabilitation interventions to improve locomotion post-stroke, including providing multiple exercises targeting impairments and activity limitations, is uncertain. Emerging evidence rather suggests attempts to prioritize stepping practice at higher cardiovascular intensities may facilitate greater locomotor outcomes. Objective: The present study was designed to evaluate the comparative effectiveness of high-intensity training (HIT) to usual care during inpatient rehabilitation post-stroke. Methods: Changes in stepping activity and functional outcomes were compared over 9 months during usual-care (n = 131 patients < 2 months post-stroke), during an 18-month transition phase with attempts to implement HIT (n = 317), and over 12 months following HIT implementation (n = 208). The transition phase began with didactic and hands-on education, and continued with meetings, mentoring, and audit and feedback. Fidelity metrics included percentage of sessions prioritizing gait interventions and documenting intensity. Demographics, training measures, and outcomes were compared across phases using linear or logistic regression analysis, Kruskal-Wallis tests, or χ 2 analysis. Results: Across all phases, admission scores were similar except for balance (usual-care>HIT; P < .02). Efforts to prioritize stepping and achieve targeted intensities during HIT vs transition or usual-care phases led to increased steps/day ( P < .01). During HIT, gains in 10-m walk [HIT median = 0.13 m/s (interquartile range: 0-0.35) vs usual-care = 0.07 m/s (0-0.24), P = .01] and 6-min walk [50 (9.3-116) vs 2.1 (0-56) m, P < .01] were observed, with additional improvements in transfers and stair-climbing. Conclusions: Greater efforts to prioritize walking and reach higher intensities during HIT led to increased steps/day, resulting in greater gains in locomotor and non-locomotor outcomes.